Pemanfaatan Smartphone Untuk Pembuatan Video Bagi Siswa Broadcasting dan Perfilman Di SMKN 7 Padang - Widya Wahyuni; Mutia Rahmi Dewi; Sumema; Angga Putra Arlis; Elfia Sukma; Sri Dewi Angguni (Pusat Riset dan Inovasi Nasional, 2025)
This community service program aims to improve the competencies of students at SMKN 7 Padang in smartphone-based video production. The training was designed to bridge the skills gap between the creative industry’s demands and the students’ current abilities, particularly those in the Broadcasting and Filmmaking department. The implementation used a participatory approach through several stages: needs assessment, material development, technical training, production practice, editing using CapCut, and evaluation through questionnaires. A total of 40 students participated and were divided into four groups to support collaborative practice. The results show significant improvement in both technical skills and creativity. Participants successfully produced audiovisual works based on scripts and demonstrated progress in shooting, editing, and digital publication. Questionnaire results indicated very high satisfaction levels, with implementation indicators above 71% and outcome indicators above 90%, reflecting the program’s effectiveness in enhancing students’ knowledge and skills. Recommendations include advanced training on directing, advanced editing, YouTube channel management, and strengthened collaboration between higher education institutions and schools.